2013
DOI: 10.1186/1678-9199-19-25
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of a novel palladium (II) complex lethality with bee venom on the human T-cell acute lymphoblastic leukemia cell line (MOLT-4)

Abstract: BackgroundAlthough honeybee venom (BV) has been reported to induce apoptosis in different types of cancerous cells, its synergistic effects with customary anti-cancer drugs remain largely unknown. In the present study, we evaluated the cytotoxic effect of BV alone (as a natural product) and the synergistic cytological effects of this component in combination with [Pd (bpy) (Pi-Pydtc)]NO3 – a novel palladium complex on human T-cell lymphoblastic leukemia cells. To investigate the cytotoxic effect of the BV alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Other authors also noticed joint effects of BV and MEL on the cytotoxicity of cytostatic drugs in different cancer cells (Oršolić 2009;Alizadehnohi et al 2012;Safaeinejad et al 2013;Choi et al 2014). Oršolić (2009) observed potentiation of BV cytotoxicity with the DNA-damaging drug bleomycin on HeLa and Chinese hamster lung fibroblast V79 cells.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other authors also noticed joint effects of BV and MEL on the cytotoxicity of cytostatic drugs in different cancer cells (Oršolić 2009;Alizadehnohi et al 2012;Safaeinejad et al 2013;Choi et al 2014). Oršolić (2009) observed potentiation of BV cytotoxicity with the DNA-damaging drug bleomycin on HeLa and Chinese hamster lung fibroblast V79 cells.…”
Section: Discussionmentioning
confidence: 93%
“…Alizadehnohi et al (2012) also showed that effects of cDDP in ovarian cancerous cDDP-resistant A2780cp cells could be enhanced by the addition of a non-lethal dose of BV. Most recently, Safaeinejad et al (2013) evaluated the synergistic cytological effects of BV and novel palladium (II) complex [Pd (bpy) (Pi-Pydtc)]NO 3 on human T-cell lymphoblastic leukemia MOLT-4 cells. They also found a clear synergistic effect of BV on a Pd complex and the apoptotic pathway activated by BV in combination with Pd complex was caspase-3-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, using BV and melittin induces extensive hemolysis and toxicity of the cells, a severe side effect that limits their future development and clinical application. Ongoing research is addressing practical issues including standardization, toxicity, and stability [97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%